Միջնադարյան աղբյուրները Թորգոմի, Թորգոմանց, Թորգոմանց տան մասին - Գ. Ա. Ջանոյան (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Согласно данным армянских и грузинских исторических источников, отцом Хайоса, Картлоса, Раноса и родоначальников других кавказских племен являлся Торгом, разделивший свою страду Тогарму—дом Торгома между сыновьями и назначивший правителем над ними Хайка. According to the facts of Armenian and Georgian historical sources, Torgom was the father of Hayos, Kartlos, Ranos and ancestors of other Caucasian tribes, dividing his country Togarmu-house of Torgom into hie sons and appointing Haik as the governer above them.
Keywords: History; Auxiliary Sciences of History; Genealogy; D History